Structure and Function of the Fecal Microbiota in Diarrheic Neonatal Piglets - Yang, Qiaoli; Huang, Xiaoyu; Zhao, Shengguo; Sun, Wenyang; Yan, Zunqiang; Wang, Pengfei; Li, Shenggui; Huang, Wangzhou; Zhang, Shengwei; Liu, Lixia; Gun, Shuangbao (Frontiers in Microbiology, 2017)
Diarrhea is a leading cause of increased mortality in neonatal and young piglets. Aberration of the gut microbiota is one important factor in the etiology of piglet diarrhea. However, information regarding the structure and function of the gut microbiome in diarrheic neonatal piglets is limited. To investigate the composition and functional potential of the fecal microbiota in neonatal piglets, we performed 16S rRNA gene sequencing on 20 fecal samples from diarrheic piglets and healthy controls, and metagenomics sequencing on a subset of six samples. We found striking compositional and functional differences in fecal microbiota between diarrheic and healthy piglets. Neonatal piglet diarrhea was associated with increases in the relative abundance of Prevotella, Sutterella and Campylobacter, as well as Fusobacteriaceae. The increased relative abundance of Prevotella was correlated with the reduction in E. coli and the majority of beneficial bacteria that belonging to the Firmicutes phylum (e.g., Enterococcus, Streptococcus, Lactobacillus, Clostridium, and Blautia) in diarrheic piglets. The differentially functional gene abundances in diarrheic piglets were an increase in bacterial ribosome, and contributed primarily by the genera Prevotella, this indicates a growth advantage of the Prevotella in diarrheic conditions. Additional functional gene sets were associated with the reduction of polyamine transport, monosaccharide and sugar-specific PTS transport, amino acid transport, and two-component regulatory system. These profiles likely impact the ability to transport and uptake nutrients, as well as the ability to fight microbial infections in the piglet gut ecosystem. This work identifies a potential role for Prevotella in the community-wide microbial aberration and dysfunction that underpins the pathogenesis of piglet diarrhea. Identification of these microbial and functional signatures may provide biomarkers of neonatal piglet diarrhea.